“A Pole Is a Selfless Host”. Old Polish Hospitality, or a Post-Partition Phantasm - Śnieżko, Dariusz (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
The article discusses the image of Old Polish hospitality in the version presented by Polish writers of Post-Partition era. The analysis conducted uses the categories of myth, stereotype and phantasm. In the conclusion, the material is interpreted in the supernatural, ethical, aesthetic and political order.